The Morbidity and Mortality of Surgery for Traumatic Brain Injury in Geriatric Patients: A Study of Over 100 000 Patient Cases. Issue 6 (8th October 2021) - Haddad, Alexander F; DiGiorgio, Anthony M; Lee, Young M; Lee, Anthony T; Burke, John F; Huang, Michael C; Dhall, Sanjay S; Manley, Geoffrey T; Tarapore, Phiroz E
Abstract: BACKGROUND: Geriatric patients have the highest rates of Traumatic Brain Injury (TBI)-related hospitalization and death. This contributes to an assumption of futility in aggressive management in this population. OBJECTIVE: To evaluate the effect of surgical intervention on the morbidity and mortality of geriatric patients with TBI. METHODS: A retrospective analysis of patients ≥80 yr old with TBI from 2003 to 2016 was performed using the National Trauma Data Bank. Univariate and multivariate analyses were performed to compare outcomes between surgery and nonsurgery groups. RESULTS: A total of 127 129 patient incidents were included: 121 185 (95.3%) without surgery and 5944 (4.7%) with surgery. The surgical group was slightly younger (84.0 vs 84.3, P < .001) and predominantly male (60.2% vs 44.4%, P < .001). Mean emergency department (ED) Glasgow Coma Scale (GCS) was lower in surgical patients (12.4 vs 13.7, P < .001). Complications (OR = 1.91, CI:1.80-2.02, P < .001) and hospital length of stay (LOS, ß = 5.25, CI:5.08-5.42, P < .001) were independently associated with surgery. Intensive care unit (ICU) LOS (ß = 3.19, CI:3.05-3.34, P < .001), ventilator days (ß = 1.57, CI:1.22-1.92, P < .001), and reduced discharge home (OR = 0.434, CI:0.400-0.470, P < .001) were also independently associated with surgery. However, surgery was not independently associated with mortality on multivariate analysis (OR = 1.03, CI:0.955-1.12, P = .423). Recursive partitioning analysis identified ED GCS and injury severity score (ISS) as prognosticators of mortality following surgical intervention. CONCLUSION: Surgical treatment of geriatric patients with TBI is associated with increased complications, hospital LOS, ICU LOS, and ventilator days as well as reduced discharge to home. However, surgery is not associated with increased mortality. ISS and ED GCS are prognosticators of mortality following surgical intervention. Graphical Abstract: